Development Area by Using City Image Perception Based on Patterns of the Land Use - Khamwachirapithak, Putpunnin (Journal of Architectural/Planning Research and Studies (JARS), 2017)
This article aims to analyze image perception in land based on patterns of the land use: dispersed and compact patterns. The main purposes of the study are: 1) to study patterns and types of building and land use in the target universities in order to be representative of dispersed and compact patterns, 2) to evaluate image perception, and 3) to raise issues and proper development on city image perception based on patterns of the land use. The results show that Thammasat Rangsit campus has been considered as a representative of dispersed pattern because of low intensity of building and land use. Non-fully potential land use. The participants felt that it is difficult to engage in image perception when entering into the place, got lost, due to the complicated structure of the land. Image perception is suggested to be brought as a facilitating factor dictating travelling behavior. The cognition in network of the route and recognisable symbol can be applied by installing a clear indicating sign at the most recognisable points. Srinakharinwirot Prasarnmit campus, it has been considered as a representative of compact pattern of land use. This is due to the fact that the university has an effective land management. Even though the place has a limitation in size, and a high intensity of building and land use are found, yet, the image perception shows that the participants were not nearly get lost. They felt that the land is complicated. A navigation, directional sign and referable points are recommended to solve the problem.